ANALISIS EFISIENSI PENGGUNAAN PONDASI BORED PILE PADA PROYEK PEMBANGUNAN RUMAH SUSUN ASN UNIVERSITAS ANDALAS - Benny Viske; Elfania Bastian; Asiya Nurhasanah Habirun (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
The construction of the Andalas University ASN flats has been built in the Andalas University area. This building was realized by the Directorate General of Housing of the Ministry of Public Works dan Public Haousing using 3-storey reinforced concrete construction with a building height of 22.63 m and hard soil conditions. The foundation is a very important structural element in a building. The foundation is defined as an underground structure that transmits the loads originating from the weight of the building itself and the loads acting on the building to the surrounding soil. The foundation used in the construction of ASN Andalas University flats is a bored pile foundation with a diameter of 1 meter. The purpose of this paper is to calculate the bearing strength of bored piled used as the foundation based on sondir data. By using the Meyerhoff method, the result of calculatating the bearing capacity of the foundation at foundation point A1, A16, D1 and D16 obtained Qult = 251,98 kN. While the Calculation of bearing capacity using the Schmertmann-Nottingham method at foundation point A1 obtained Qult = 439.01 kN, at foundation point A16 obtained Qult = 320,12 kN, at foundation point D1 obtained Qut = 530.47 kN and foundation point D16 obtained Qult = 288,11 kN. This calculation uses sondir 3 data. Based on the calculation results of ETABS v9.7.4 Pu = 389.572 kN, the calculation of the carrying capacity using the MAyerhoff method is not safe to use. Whereas using the Schmertmann-Nottingham method, only two foundation points are safe to use, namely at the foundation point A1 and D1. Keywords: Foundation, Sondir, bearing capacity, Bored Pile, Metodde Mayerhoff Schmertmann–Nottingham